THE EFFECT OF PROJECT BASED LEARNING ON SCIENCE PROCESS SKILLS IN EARLY CHILDREN - Dessy Farantika; Dwi Indrawati; Arif Muzayin Shofwan; Rina Insani Setyowati (-, 2022)
The results of preliminary observations indicate that learning still uses Project Based Learning Model Learning. So that the child's ability to speak is still lacking, especially telling the contents, communicating with simple words, expressing ideas, retelling the story according to the flow. The right learning model to stimulate children's speaking ability is Project Based Learning assisted by big books, because project learning is carried out in groups and uses big book media so that it can stimulate children's speaking abilities. The purpose of this study was to determine the differences in group learning outcomes using the Project Based Learning model assisted by big books and the Project Based Learning class groups on speaking skills.  The study design uses quasi-experimental research. The subjects in this study were all children of group B in TK Al-Muhajirin Malang in the 2018/2019 academic year even semester which consisted of two classes namely B1 totalling 17 children as an experimental class and B2 totalling 17 children as a control class, using purposive sampling. The prerequisite test used in this study was the construct validation test with 3 validators, namely one lecturer as a learning expert, one lecturer as a media expert, and one school principal as a practitioner to assess the validity level of the Daily Learning Implementation Plan (RPPH) and an observation sheet of participants' speaking skills students using big book.